ICTs for Modernizing Government in Africa - Mukherjee, Kamal; Alexander, Trish; Graaf, Liezl De; Zyl, Omri Van (World Bank, Washington, DC, 2014)
ICT is fundamentally changing the way in which government representatives, citizens, business and other agents of the state interact throughout the world as well as in Africa. The public service sector has strategic significance as it impacts not only on the well-being of individuals, families and communities and on individual national governments but indirectly on the stability of the global economy. The associated high expectations, particularly regarding the speed and flexibility with which public service providers can respond to individual requests, provide feedback on programs and expenditure and handle national crises, are extremely challenging. Efficient service delivery is frequently hampered by program developers who do not listen sufficiently carefully to the poor and hence are not able to identify their needs and prioritize them. Planning that focuses on supplier interests rather than those of the end-user is also a problem.